Exploring the effect of problem based facilitatory teaching approach on motivation to learn: a quasi-experimental study of nursing students in Tanzania - Walter C. Millanzi; S. M. Kibusi (BMC Nursing, 2021)
Abstract Background Academic motivation is most important as a key determinant of competent and motivated nurses who are often considered as frontline healthcare providers who devote most of their time taking care of clients and patients. However, most of them demonstrate remarkable differences in their academic performances during their schooling that might be due to the differences in their academic motivation and achievement motivation. There appears a growing concern to rethink the approaches on how nurses are prepared, explore, and test novel approaches for delivering the nursing curricula. This study tested the effect of Problem Based Facilitatory Teaching pedagogy on academic motivation among nursing students in Tanzania, higher learning institutions. Methods A pre-post-test controlled quasi-experimental study of 401 purposively selected participants was conducted between February and June 2018. The study was not a clinical randomized controlled trial and thus it has not been identified in the title and no summary of trial design, its methods, results, and conclusion. The Auditing Inventory developed by the researcher measured the intervention and a Questionnaire titled “Academic Motivation Scale,” was adopted to measure academic motivation. Statistical Product for Service Solutions software program version 23 was used to perform descriptive analysis to establish participants’ sociodemographic profiles. Regression analysis was performed to determine the association between variables. Results Findings revealed that 65.8% of participants were males. Post-test findings showed 70.3% of participants demonstrated the motive to learn contrary to 34.9% at baseline. The odds of an intervention to influence academic motivation among participants was higher than the control (AOR = 1.720; p < 0.05; 95%CI: 1.122, 2.635). However, the intervention demonstrated little influence on the extrinsic motivation to learn (AOR = 0.676, p > 0.05, 95%CI: 0.405, 1.129) and Amotivation to learn (AOR = 0.538, p > 0.05; 95%CI: 0.283, 1.022) compared to the control. Conclusion The Problem Based Facilitatory Teaching pedagogy was a predictive factor to intrinsic academic motivation among nursing students. The approach demonstrated educational potentials to change the spectrum of nursing competency and quality of care to patients or clients. This study suggests problem-based facilitatory teaching pedagogy be integrated into the nursing curriculum in Tanzania as it is feasible.